EJEMPLOS DE ANOMALÍAS DEL RADÓN 222 COMO PRECURSORAS DE EVENTOS SÍSMICOS EN COSTA RICA. - García-Vindas, J. R. (2011)
The relation between seismicity and Radon – 222 concentration anomalies has been studied. Thechanges in the gas concentration are considered as precursors of the seismic events. This study illustrates the before mentioned relation and confirms that aquifers are favorable places for radon monitoring.